ADHERENCE TO ANTIHYPERTENSIVE MEDICATION AND ITS DETERMINANTS IN A PRIMARY CARE SETTING OF KALABURAGI DISTRICT - GEETHANJALI P; POONAM P SHINGADE; AMRUTA SWATI I; PRASHANT KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Hypertension is a chronic condition of concern and it is the most common non-communicable disorder posing a major public health challenge in many aspects. Adherence to prescribed medicine is a crucial issue that is directly related to the management of hypertension. To control high blood pressure and to avoid associated repercussions, good antihypertensive medication adherence is an effective strategy. The study aimed to estimate adherence to medication among hypertensive patients attending the non-communicable disease clinic at Urban Primary Health Centre (UPHC), Kalaburagi. To assess the determinants of adherence to antihypertensive medication. Methods: A facility-based cross-sectional study was conducted among adult hypertensive patients receiving treatment from the UPHC. A semi-structured questionnaire and an 8-item Morisky medication adherence scale (MMAS-8) were used to assess the determinants and medication adherence status. Results: Assessing the adherence level using the Morisky scale (MMAS-8), it was observed that 35 (38.9%) had low adherence, while 26 (28.9%) had medium adherence and 29 (32.2%) had high adherence. Conclusion: The majority of study participants have poor adherence to antihypertensives. The adherence level can be further improved by providing health education and efficient counseling drug adherence assessment needs to be an integral component of routine care.